Myrcia s.l. (Myrtaceae) da Reserva Natural Vale, Linhares, Espírito Santo, Brasil - Scaravelli, Fernanda (2018)
The Neotropical species of Myrtaceae, except Metrosideros stipularis, belong to the tribe Myrteae. Myrcia s.l., one of the seven groups of Myrteae, is exclusively Neotropical and comprises about 760 species (including species currently recognized as Calyptranthes). Myrcia s.l. is divided into nine monophyletic groups, which are treated as sections. The Tabuleiro Forest formation in the northern part of Espírito Santo, composed of Vale Natural Reserve, Sooretama Biological Reserve and other adjacent protected areas, is indicated as one of the main areas for Myrtaceae diversity in the state. The aim of this study is the taxonomic treatment of Myrcia s.l. in the Vale Natural Reserve. For this, field trips were made between December 2015 and January 2017 and the collections of the following herbaria were analyzed: CVRD, ESA, RB, RBR, SORO, SP, SPSF. There are 48 species of Myrcia s.l. and eight sections in the area. Myrcia sect. Aulomyrcia (18 spp.) is the richest section, followed by “Myrcia sect. Gomidesia” (nine spp.), “Myrcia sect. Calyptranthes” (six spp.), Myrcia sect. Myrcia (five spp.), “Myrcia sect. Eugeniopsis”, Myrcia sect. Sympodiomyrcia (three spp. each) and “Myrcia sect. Aguava” and “Myrcia sect. Reticulosa” (two spp. each). Identification keys, taxonomic descriptions and comments of species are presented.